Seed and feeder use by birds in the United States and Canada. (1st November 2013) - Horn, David J.; Johansen, Stacey M.; Wilcoxen, Travis E.
ABSTRACT More people feed birds and other wildlife than hunt and fish combined. Despite its popularity, many bird‐feeding traditions lack scientific data. We examined seed and feeder use by wild birds in the United States and Canada, and how seed use may change by season and geographic region. Between 2005 and 2008, 173 individuals from 38 states and 3 provinces in Canada made 20, 077, 45‐minute observations at bird feeders, recording 106 species and 1, 282, 424 bird visits. Of the 10 seed types most commonly used in bird seed blends, 3 are most attractive to birds: black‐oil sunflower, medium sunflower chips, and white proso millet. Other seeds such as red milo are less attractive. Chickadees (Poecile spp.), nuthatches (Sitta spp.), and larger finches (Carpodacus spp.) were most abundant at black‐oil sunflower, smaller finches (Carduelis spp.) were most abundant at Nyjer® (Wild Bird Feeding Institute, Chicago, IL) and sunflower chips, and sparrows (Spizella spp.) were most abundant at white proso millet. Bird‐feeding traditions have been widely reported in books, magazines, newspaper articles, and websites. These traditions are often conflicting and have not been verified empirically. Studies such as this can be used to develop scientifically based recommendations that can lead to a better bird‐feeding experience and that attract fewer species with known negative ecological consequences. © 2013 The Wildlife Society.